2009
DOI: 10.1016/j.micpath.2009.04.015
|View full text |Cite
|
Sign up to set email alerts
|

The structurally similar, penta-acylated lipopolysaccharides of Porphyromonas gingivalis and Bacteroides elicit strikingly different innate immune responses

Abstract: Lipid A structural modifications can substantially impact the host's inflammatory response to bacterial LPS. Bacteroides fragilis, an opportunistic pathogen associated with life-threatening sepsis and intra-abdominal abscess formation, and Bacteroides thetaiotaomicron, a symbiont pivotal for proper host intestinal tissue development, both produce an immunostimulatory LPS comprised of penta-acylated lipid A. Under defined conditions, Porphyromonas gingivalis, an oral pathogen associated with periodontitis, also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 48 publications
4
64
0
Order By: Relevance
“…Taken all together, our results support the idea that a relatively large variety of oral species can gain access to the intestinal microbiota, regardless of the periodontal status. Whether these microorganisms colonize or not this body site, they may cause disturbances in this environment by releasing metabolites and cell components, which induce an inflammatory state [76]. They may also interact and enhance the pathogenic effects of other species that colonize the gut [77].…”
Section: Discussionmentioning
confidence: 99%
“…Taken all together, our results support the idea that a relatively large variety of oral species can gain access to the intestinal microbiota, regardless of the periodontal status. Whether these microorganisms colonize or not this body site, they may cause disturbances in this environment by releasing metabolites and cell components, which induce an inflammatory state [76]. They may also interact and enhance the pathogenic effects of other species that colonize the gut [77].…”
Section: Discussionmentioning
confidence: 99%
“…P. gingivalis ATCC 33277 was obtained from our stock collection. The isogenic mutant strain P. gingivalis 1626KO exhibits a lipid A phenotype that is characteristic of P. gingivalis grown in hemin (1 g/ml), which represents low-hemin-concentration growth conditions as described previously (1,3,5). The isogenic mutant strain of P. gingivalis designated P. gingivalis 1587KO displays penta-acylated, 4Ј-phosphorylated lipid A and lacks nonphosphorylated lipid A, as described previously (5).…”
Section: Methodsmentioning
confidence: 99%
“…Both B. thetaiotaomicron and P. gingivalis produce LPS that contains penta-acylated, monophosphorylated lipid A (3,14,30). Paradoxically, we observed that despite the high degree of lipid A structural similarity, the LPS of B. thetaiotaomicron is significantly more potent than that of P. gingivalis in stimulating TLR4-dependent innate immune responses (3).…”
mentioning
confidence: 99%
“…For instance, it has been shown that intestinal alkaline phosphatase reduces the proinflammatory potential of LPS of gut bacteria by removing the phosphate groups (159). In addition, many gut bacteria, such as Bacteroides species, seem to have a less immunogenic lipid A structure by having fewer acyl chains (160,161). The hypoacylation of lipid A is also a strategy used by pathogens such as P. aeruginosa and N. meningitidis to decrease their immunogenicity (162,163).…”
Section: Macroamphiphilic Glycolipidsmentioning
confidence: 99%